22 PERSISTENT OPIOID USE AND HEALTHCARE UTILIZATION AMONG ADOLESCENTS AND YOUNG ADULTS WITH INFLAMMATORY BOWEL DISEASE IN THE UNITED STATES. (18th January 2018) - Wren, Anava; Bensen, Rachel; Sceats, Lindsay; Yu, Helen; Wong, Jessie; Sellers, Zachary; Kin, Cindy; Park, K T
Abstract: Background: Opioids are commonly prescribed for temporary pain relief among individuals with inflammatory bowel disease (IBD); however, the efficacy of opioids for managing chronic pain is limited and risk of adverse effects is high. Emerging evidence demonstrates that a subset of individuals with IBD receive chronic opioid therapy (COT), and that adolescents and young adults (AYAs) are at particular risk of continued opioid use. The aim of this study was to evaluate persistence of COT and associated healthcare utilization among AYAs with IBD in the United States. Methods: A longitudinal retrospective analysis was conducted with a large administrative dataset from years 2007–2015. Study criteria included individuals 15–29 years old with an IBD diagnosis (Crohn's—555/K50, ulcerative colitis—556/K51). COT was classified as having at least 2 opioid drug claims on distinct dates within 1 year. To evaluate persistence of COT, Kaplan-Meier survival analyses were used for patients who met criteria for COT and remained in the database for at least 3 years following index COT use. Results: The study cohort consisted of 93, 668 individuals; 17, 084 (18.2%) received COT for at least 1 year between 2007–2015. To examine COT longitudinally, 2, 503 individuals receiving COT in an index year were followed for at least 3 years. In year 2, 30.5% of AYAs continued to receive COT, in year 3, 10.7%, and in year 4, 5.3% (See Figure 1). Individuals receiving COT for 4 years were significantly more likely to take corticosteroids, have comorbid pain, psychiatric, and substance diagnoses, visit the ED, and be hospitalized compared to those receiving COT for 1–3 years and those who did not receive COT (p<0.01). Conclusion: This study highlights that a subset of AYAs with IBD are at particular risk for continued opioid use, associated comorbidities, and increased healthcare utilization. Research is needed to explore screening and behavioral interventions for AYAs with IBD.